A novel decision strategy for a bilateral energy contract. (1st November 2019) - Anees, Amir; Dillon, Tharam; Chen, Yi-Ping Phoebe
Graphical abstract: Highlights: We propose a unified framework for the energy market at two levels. We develop a bilateral energy trading scheme for choosing a bilateral price. We develop a novel decision strategy for both seller and buyer. We conduct a series of experiments to illustrate the effectiveness of the proposed work. Abstract: Due to the relatively high transportation cost of energy in remote regions, an effective and efficient energy trading market is required. In this paper, first, we extend the idea of a smart home community architecture comprising a small number of smart homes that suit these sorts of regions. Second, we propose an energy trading market at two levels. At the top-level, global generators and global consumers participate in energy trading. At the second level, smart homes in a smart home community participate in the energy market as local generators and consumers. Third, we develop a bilateral energy trading scheme and a novel decision strategy for choosing a bilateral price for both seller and buyer. The developed strategy and energy trading schemes are more efficient than those proposed in traditional work as they require far fewer rounds for negotiations between buyers and sellers to arrive at a mutually appropriate bilateral price. Fourth, we present two distinct cases for bilateral energy trading; single seller single buyer and single seller multiple buyers and show that the latter case has more benefits for both the seller and the buyer. Lastly, we conduct a series of experiments to illustrate the effectiveness of the proposed work.